Xanthomonas campestris pv. musacearum : population diversity and the identification of potential sources of resistance from banana accessions representing the Musa diversity worldwide - Coutinho, Teresa A. (University of Pretoria, 2026)
Thesis (PhD)--University of Pretoria, 2018.